2001
DOI: 10.1038/85927
|View full text |Cite
|
Sign up to set email alerts
|

Maternal methylation imprints on human chromosome 15 are established during or after fertilization

Abstract: Prader-Willi syndrome (PWS) is a neurogenetic disorder that results from the lack of transcripts expressed from the paternal copy of the imprinted chromosomal region 15q11-q13 (refs. 1,2). In some patients, this is associated with a deletion of the SNURF-SNRPN exon 1 region inherited from the paternal grandmother and the presence of a maternal imprint on the paternal chromosome. Assuming that imprints are reset in the germ line, we and others have suggested that this region constitutes part of the 15q imprinti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
140
1
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 192 publications
(153 citation statements)
references
References 20 publications
8
140
1
4
Order By: Relevance
“…2 and Fig. S4), indicating that the methylation imprint at the PWS-IC is not erased or reset during the nuclear reprogramming process in both male and female iPSC lines, supports the widely accepted model that the PWS-IC methylation imprint is erased in the germline, established either in the germline or during the early stages of preimplantation development, and then maintained throughout development (25)(26)(27)(28). These findings suggest that the PWS-IC methylation imprint is refractory to the global erasure of epigenetic marks induced by the reprogramming process.…”
Section: As and Pws Ipscs Maintain The Appropriate Methylation Imprintmentioning
confidence: 51%
“…2 and Fig. S4), indicating that the methylation imprint at the PWS-IC is not erased or reset during the nuclear reprogramming process in both male and female iPSC lines, supports the widely accepted model that the PWS-IC methylation imprint is erased in the germline, established either in the germline or during the early stages of preimplantation development, and then maintained throughout development (25)(26)(27)(28). These findings suggest that the PWS-IC methylation imprint is refractory to the global erasure of epigenetic marks induced by the reprogramming process.…”
Section: As and Pws Ipscs Maintain The Appropriate Methylation Imprintmentioning
confidence: 51%
“…Recently, it was revealed that histone modifications are important to determine whether the DNA methylation occurs (Tamaru et al, 2001;Jackson et al, 2002). It is proposed that histone methylation at lysine 9 is a gametic imprint in the imprinting center PWS-IC (Xin et al, 2001), while cytosine methylation of the PWS-IC occurs only after fertilization (El-Maarri et al, 2001).…”
Section: Dna Methylation In Various Biological Phenomenamentioning
confidence: 99%
“…Based on the phenotypic consequences of microdeletions affecting the PWS-SRO element of the IC, the AS-SRO element of the IC, or both, we have proposed that the maternal pattern of epigenetic modification, with CpG methylation of MKRN3, NDN and SNURF -SNRPN promoters and silencing of those genes, is the default state of the imprinted domain, that the PWS-SRO is unconditionally required for a chromosome to have the paternal pattern of epigenetic modification and gene expression, and that the AS-SRO is required for a chromosome to have the maternal pattern, if the chromosome has an intact PWS-SRO. 1 In other words, the PWS-SRO acts to activate the paternal copy of the imprinted domain or keep this copy active, 6 and the AS-SRO counteracts this activity.…”
Section: Introductionmentioning
confidence: 99%